BUZZER DALAM PERSPEKTIF HADIS: (Kajian Hadis Tematik) - Muhammad Iskandar (DIRAYAH : Jurnal Ilmu Hadis, 2021)
The existence of a buzzer is a new phenomenon in society as an effect of the development of science and technology. Buzzer is a term for a person or group of people who are active on social media and whose profession is to disseminate certain content massively. At first, buzzer services were used as a marketing strategy in the business world to popularize a product. And in its development, buzzer services are used in various aspects of life, including social and political. This research is an attempt to see the existence of the buzzer from the aspect of the Hadith of the Prophet Muhammad SAW. The author assumes that even though the buzzer profession did not exist in the time of the Prophet Muhammad, the basis or guidance for the buzzer profession can be obtained by studying in depth the hadiths of the Prophet Muhammad. Therefore, this study is thematic (maudhu'i), namely by making the buzzer the main theme, then the author explores the books of hadith and takhrij hadiths that are related to buzzer activities. Primary data sources in this study are books, journals or articles related to the title of the discussion. Then refer to the main books of hadith, especially the Kutub as-Sittah and its syarah, the books of Rijal Hadith to find out the biography and quality of the narrators, and the book of Jarh wa Ta'dil as a basis for finding a way out if there are narrators or traditions that contradictory. The secondary data inthis study are all books, and journals related to the research theme.